Is New Keynesian Economics Really New? An Answer in a New Keynesian Perspective - Corrado Benassi; Alessandra Chirco; Caterina Colombo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
This paper contrasts the descriptive and normative properties of the New Keynesian general equilibrium models with those of other Keynesian paradigms, such as the neoclassical sintesi and the post Keynesian ones. We argue that the co-ordination failures, which are pivotal within the New Keynesian setup deliver an alternative picture of the market economies with respect to three key Keynesian issues: the interpretation of the failure of Say's Law, the monetary nature of the economy, the role of the state within a market economy.
Keywords: 330